Budaya Patriarki dalam Perspektif Al-Qur’an - Parhan, Parhan; Afiyah, Nur; Isyanto, Nur (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2024)
In the social system that applies in society, we often encounter disparities between men and women. This gap does not only occur within the family or household, but also becomes a culture in society, even a culture in national and state life. For this reason, this article will discuss the patriarchal culture between men and women from the perspective of the Qur'an. The method used in writing this article is literature study. Patriarchal culture is still very influential in people's lives, both in rural and urban areas. Men still dominate the social system of society in various areas of life, including economics, politics, religion and socio-culture. As a result, women become a marginalized group. Gender differences between men and women often lead to discrimination and gender injustice, and the victims are mostly women. The research results show that all humans, men and women, are equal and what differentiates them is their piety. Therefore, the assumption that male power leads to despotism towards women which is the beginning of violence against women, especially in the family, women have a lower status than men according to the Koran is not true, because Islam is a religion that glorifies women and Of course, Islam strictly prohibits acts of violence, especially violence against women.